2004
DOI: 10.1021/je0498560
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Vapor−Liquid Equilbria of Some Carbon Dioxide + Organic Binary Systems

Abstract: Vapor−liquid equilibria, molar volumes, and volume expansion for several binary mixtures of organic solvents with carbon dioxide have been determined using a visual synthetic technique at temperatures from (298 to 333) K. The binary vapor−liquid equilibrium and saturated liquid molar volume of CO2 + acetone, + acetonitrile, + dichloromethane, + nitromethane, + N-methyl-2-pyrrolidone, + perfluorohexane, + 2-propanol, + tetrahydrofuran, + toluene, and + 2,2,2-trifluoroethanol were measured at temperatures from (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 21 publications
6
73
0
Order By: Relevance
“…5, experimental results of vapor-liquid equilibria for CO 2 + tetrahydrofuran system at 60 • C are shown. Solubilities of CO 2 in tetrahydrofuran were in good agreement with literature values [14]. The apparatus and procedures were determined to be reliable.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…5, experimental results of vapor-liquid equilibria for CO 2 + tetrahydrofuran system at 60 • C are shown. Solubilities of CO 2 in tetrahydrofuran were in good agreement with literature values [14]. The apparatus and procedures were determined to be reliable.…”
Section: Resultssupporting
confidence: 84%
“…As shown in Fig. 4 for the CO 2 + tetrahydrofuran system, the viscosity decreased with increasing CO 2 mole fraction and the density slightly increased with increasing CO 2 mole Bubble-point pressures obtained for the CO 2 + tetrahydrofuran system at temperature of 60 • C compared with vapor-liquid equilibria data in the literature [14]. Filled circles represent this work, unfilled circles, squares represent literature data [14] fraction.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Ternary phase diagrams have been calculated using the measurements recorded using the sapphire cell technique [11][12][13] . Using the following material balances, two specific ternary phase diagrams were constructed as shown in Figures 5 and 6.…”
Section: Representative Resultsmentioning
confidence: 99%
“…On the phase equilibrium data for carbon dioxide + THF mixtures, Im et al [2] [3] had reported VLE, molar volume, and volume expansion data at 298, 313, and 333 K by the PTx method using Patel-Teja equation of state from the measurements of the carbon dioxide and THF initially loaded and the total vapor volume. However, the experimental data of molar volume and volume expansion data seem to be a low accuracy because there are some problems in the experimental procedures.…”
Section: Introductionmentioning
confidence: 99%